2017
DOI: 10.1016/j.cyto.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

L-leucine dietary supplementation modulates muscle protein degradation and increases pro-inflammatory cytokines in tumour-bearing rats

Abstract: Cancer cachexia is characterised by involuntary weight loss associated with systemic inflammation and metabolic changes. Studies aimed at maintaining lean body mass in cachectic tumour-bearing hosts have made important contributions reducing the number of deaths and improving the quality of life. In recent years, leucine has demonstrated effective action in maintaining lean body mass by decreasing muscle protein degradation. Currently, there is a growing need to understand how leucine stimulates protein synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 37 publications
6
45
0
1
Order By: Relevance
“…Muscle atrophy F-box (MAFBX) and muscle Ring finger 1 (MURF-1) are responsible for increased protein degradation through the UPP pathway, which can actually be considered the master genes for muscle atrophy and wasting [39,45,46]. Leu could increase muscle protein deposition by regulating protein synthesis and protein degradation in mammals [29,47]. Dietary optimal Leu up-regulated liver TOR mRNA expression in juvenile hybrid grouper and juvenile blunt snout bream [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle atrophy F-box (MAFBX) and muscle Ring finger 1 (MURF-1) are responsible for increased protein degradation through the UPP pathway, which can actually be considered the master genes for muscle atrophy and wasting [39,45,46]. Leu could increase muscle protein deposition by regulating protein synthesis and protein degradation in mammals [29,47]. Dietary optimal Leu up-regulated liver TOR mRNA expression in juvenile hybrid grouper and juvenile blunt snout bream [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that leucine uses the insulin signalling pathway, but the exact mechanism of triggering the mTOR complex remains under debate [25]. Nutritional supplementation with leucine stimulated the incorporation of phenylalanine in muscle in an experimental cachexia model, confirming an increased protein synthesis and also an increasing muscle mass [26,27]. Subunits of the mTORC1 complex (i.e., Raptor and GβL) and substrates belonging to the downstream pathway (i.e., 4E-BPs, eIF4A, eIF4B, eIF4E, including S6K1), which represent the key points within the metabolism of proteins through mTOR, are highly increased in the muscle of Walker-256 tumour-bearing animals subjected to leucine nutritional supplementation [27][28][29].…”
Section: Muscle Protein Synthesis and Leucinementioning
confidence: 99%
“…Proteasome degradation results in 7-9 amino acid peptides, which are subsequently degraded by cytosolic proteases. During muscle wasting, the activity of chymotrypsin is increased, as is the expression of 19S, 11S, and 20S, all of which are modulated by the nutritional supplementation of leucine [27,65,66].…”
Section: Proteolytic Pathways and Leucinementioning
confidence: 99%
“…Our previous studies have shown that the Walker 256 tumour growth-an experimental model of cachexia-led to metabolomic [13] and metabolic [14] alterations, and increased the muscle proteasomal activity [15,16] in adult rats. However, to the best of our knowledge, the biomarkers-related to sarcopenia and cachexia in senile cancer animals are not yet totally known.…”
Section: Introductionmentioning
confidence: 99%